TU ESCUELA EN CASA: IN TIMES OF PANDEMIC GUIDELINES FOR EDUCATION IN PARAGUAY - Sotille Riedi, André Luis; Nascimento Pereira, Eliane; Camacho Bezerra, Renata [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2022)
Paraguay, through its Ministry of Education and Sciences, created the National Plan for Education in Times of Pandemic Tu Escuela en casa, which defined guidelines for education in the period of the COVID-19 pandemic, due to the suspension of classroom classes. The aim of this article is to present the Paraguayan plan and the perceptions of society in its implamation. The study is of a qualitative nature and has an interpretative character, in which it was found that the main challenges for the implementation of the plan were the infrastructure of the educational system, internet connectivity and teacher training. On the other hand, it highlights the importance and concern that the country delegates education when preparing a National Plan for the pandemic period, the flexibility of the Plan in the face of adversities and cultural differences and, the participation of different sectors in the elaboration and implementation of this plan.
TU ESCUELA EN CASA: DIRETRIZES PARA EDUCAÇÃO EM TEMPOS DE PANDEMIA NO PARAGUAI
Keywords: COVID-19; Educational directives; Emergency Remote Education; National Plan